Evaluation of Humanity Collegian Females’ Sedentary Behaviors in the University of Baghdad - Noora Hama Karim, MScN; Dr. Mohammed Fadhil Khalifa, PhD (Genius Journals, 2022)
Background: Sedentary behaviors are poorly understood, despite the fact that it has reached pandemic proportions and is now a major public health issue. Objectives: This study aimed to evaluate the humanity collegian females’ sedentary behaviors. Methods: A cross-sectional study is conducted through the period of January10th, to November 1st, 2021 to evaluate the humanity collegian females’ sedentary behaviors at the University of Baghdad, the study employs a purposive (non-probability) sampling technique to select (eighty) female students in College of Education for Women and College of Languages, (forty) collegian females from each college with inclusion criteria: 1) Collegian females whose ages are between (18-21) years old; 2) single, 3) free of chronic diseases. The questionnaire comprises 18 questions about time spent sitting in five basic domains, including meals, transportation, studying, screen time, and other activities, as well as sleeping/napping time on the previous day.
Keywords: Collegian; Sedentary Behaviors; questions; Women